Peran LSM LPA dalam Melindungi Hak Anak Down Syndrome Korban Kekerasan Seksual di Deli Serdang - Dicky Kurniawan; Hairani Siregar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Sexual violence against children is a highly complex issue with profound negative impacts on both the victims and their social environment. Children with disabilities, particularly those with Down Syndrome, are among the most vulnerable to such abuse due to their physical and cognitive limitations. Given this context, the role of non-governmental organizations (NGOs) such as the Child Protection Agency (LPA) becomes crucial. LPA plays a vital role in providing support, advocacy, and assistance to child victims of sexual violence, especially those with disabilities. This study aims to examine the protective role of LPA in assisting children with Down Syndrome who have become victims of sexual violence in Deli Serdang Regency. Using a qualitative method with a phenomenological approach, the research explores and interprets the lived experiences of informants involved in the cases. The study also highlights the implementation of the four child protection principles as applied by the LPA. The findings show that LPA fulfills its protective role by providing legal assistance, psychosocial support, and ensuring the safety of the victims. The organization successfully implemented the four child protection principles, resulting in a 12-year prison sentence for the perpetrator and justice for the victim. The study recommends increasing LPA staff capacity to enhance the quality of services provided.